CHROMOGRANIN-POSITIVE ALDOSTERONE-PRODUCING ADRENOCORTICAL CARCINOMA WITH CORTISOL CO-SECRETION: A CASE REPORT - Balina, Megan Margrethe (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 45-year-old Filipino female consulted due to persistent bilateral lower-extremity weakness associated with poorly-controlled hypertension on triple anti-hypertensive medications, recurrent spontaneous hypokalemia, elevated plasma aldosterone concentration (PAC), suppressed plasma renin activity (PRA), elevated PAC/PRA ratio at 318.29 ng/dL per ng/mL/hour, and a nonsuppressed 8 am serum cortisol at 11.6 ug/dL after 1 mg overnight dexamethasone suppression test. A computed tomography scan of the abdomen (adrenal protocol) showed a heterogeneously enhancing right adrenal mass measuring 6.2 x 6.5 x 9.5 cm (previously 4.6 x 5.3 x 6.3 cm), exhibiting intralesional vascularity and areas of necrosis, with mass effect to the liver, right kidney, and inferior vena cava. She underwent an open right adrenalectomy with the removal of a 9.5 x 6.8 x 5.0 cm encapsulated mass. The histopathology report revealed a low-grade adrenocortical carcinoma.